(untitled) (Environmental Smoke, 2026)
The IV Tilapia Business Fair of Jatobá (FENTIJA), held on August 15–16, 2025, established itself as a platform for integration among producers, researchers, students, educational institutions, and companies in the aquaculture sector, strengthening the interaction between science, technological innovation, and regional development. Under the theme “Technological Innovation in Fish Farming: Pathways to Sustainable Production,” the 2025 edition highlighted technological solutions to modernize fish farming, combining productive efficiency, economic viability, and socio-environmental responsibility. This e-book compiles technical, scientific, and extension abstracts, including works from the Junior Category (High School), showcasing the diversity of experiences and reaffirming the commitment to innovative, efficient, competitive, and environmentally responsible fish farming.